English Teachers' Conceptual Knowledge and Pedagogical Practices on Student-Centered Learning in Primary Schools in Denpasar Municipality - Dewi, A.A.R. Candra (Universitas Pendidikan Ganesha, 2019)
This study aims at (1) describing the conceptual pedagogical knowledge of the English teachers in public elementary schools in Denpasar municipality on child-centered learning, (2) describing the pedagogical practices of the English teachers in public elementary schools in Denpasar municipality on child-centered learning, and (3) describing the relation of English teachers’ conceptual pedagogical knowledge and pedagogical practices in the context of child-centered learning in public elementary schools in Denpasar municipality. The subjects who are under investigation in the study are three English primary teachers from three public primary schools in Denpasar municipality. The type of this study is embedded mixed method which was adapted from Creswell (2012). The instruments used to collect the data in this study are observation sheet, questionnaire, and interview guide. The result of the questionnaire shows that the Teachers have very strong concept on child-centered learning as the mean score is in the range of 3.3335 ≤ M ≥ 4.0005. This was contradicted with the data obtained from the classroom observation in which implementation of child-centered learning was low implemented. It indicated that there was tendency of inconsistent between teachers' conceptual knowledge and their practices on child-centered learning